Contemplar y poseer. El poder de la mirada en la disputa por la apropiación de objetos y monumentos de las culturas antiguas de Centroamérica - Alvarenga Venutolo, Patricia (Revista de historia., 2015)
The dialogue between the narratives written by the Corregidor del Petén Modesto Méndez and the northamerican diplomatic J. L. Stephens about the discovery of the ruins of Tikal, located in Guatemala by the first and Copán and Quiruguá, in Honduras and Guatemala respectively by the second. The goal of this article consist in analyze the arguments of travelers and scientific to justify their appropriation of archaeological wealth as well as the scope of the answers given by the subjects from subaltern countries to such appropriation. This article develops the issue of “esthetic contemplation.” From the prospective of whom coming from the hegemonic countries, the esthetic contemplation is an exclusive attribute of them that establishes a radical distance between them and the nations located at the south of the world. This text explores how Méndez responds to such a conception in order to observe the reach of his challenge to colonial system. Furthermore, the article has two other prospectives: it put in dialogue the narrative de Méndez y Stephens with the narrative related to ancestral monuments coming from the previous centuries in order to explore the changes in their representation that the modernity introduced. Secondly, these pages analyze how Mendez was read by an actor of the Guatemalan Revolution (1944-1954) Hugo Cerezo Dardón in order to explain why such discourse acquire such a signification during the process of national formation prompted by the revolutionary state.